Cold tolerance in the genus Arabidopsis. Issue 3 (24th February 2020) - Armstrong, Jessica J.; Takebayashi, Naoki; Wolf, Diana E.
Abstract : Premise: Cold tolerance is an important factor limiting the geographic distribution and growing season for many plant species, yet few studies have examined variation in cold tolerance extensively within and among closely related species and compared that to their geographic distribution. Methods: This study examines cold tolerance within and among species in the genus Arabidopsis . We assessed cold tolerance by measuring electrolyte leakage from detached leaves in multiple populations of five Arabidopsis taxa. The temperature at which 50% of cells were lysed was considered the lethal temperature (LT50 ). Results: We found variability within and among taxa in cold tolerance. There was no significant within‐species relationship between latitude and cold tolerance. However, the northern taxa, A. kamchatica, A. lyrata subsp. petraea, and A. lyrata subsp. lyrata, were more cold tolerant than A. thaliana and A. halleri subsp. gemmifera both before and after cold acclimation. Cold tolerance increased after cold acclimation (exposure to low, but nonfreezing temperatures) for all taxa, although the difference was not significant for A. halleri subsp. gemmifera . For all taxa except A. lyrata subsp. lyrata, the LT50 values for cold‐acclimated plants were higher than the January mean daily minimum temperature (Tmin ), indicating that if plants were not insulated by snow cover, they would not likely survive winter at the northern edge of their range. Conclusions: Arabidopsis lyrata and A. kamchatica were far more cold tolerant than A. thaliana . These extremely cold‐tolerant taxa are excellent candidates for studying both the molecular and ecological aspects of cold tolerance.